Evaluasi Pemenuhan Permenaker No.04/MEN/1980 dan SKEP/100/xi/1985 Terhadap Alat Pemadam Api Ringan di PT. Angkasa Pura I Bandar Udara Ahmad Yani Semarang - Kristianto, Dhito Hadi; Ekawati, Ekawati; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (Undip), 2015)
Catastrophic fires as an undesirable events are always good material losses, the human soul as well as the environment. Planning countermeasures of fire (Fire Safety) is to save souls and then avoid damage intensity as minimum as possible. Based on the results of the initial survey on the Check-In area, Light of fire Extinguishers as one of the fire extinguishers at PT. Angkasa Pura I Ahmad Yani Airport does not comply with the provisions of PERMENAKER No. 04/MEN/1980. This study aims to evaluate the application of light-weight Fire Extinguishers according to regulations. This research is qualitative research with type a descriptive method. Sample research consists of 5 main buildings and one informant informant triangulation chosen directly by the researchers. Measuring instrument which is used in the form of a check list, and guidelines for the interview. The data were analyzed using qualitative analysis results are presented in the form of a narrative (description). The results showed that as much as 60% installation is in compliance with regulations of the APAR, maintenance carried out for three months, the condition still exists as yet APAR ready-to-wear. Conclusion the research that is both fitting, Fire Extinguishers Mild conditions, maintenance of Fire Extinguishers and the use by employees is in compliance with the provisions of the existing provisions.